Does Location Matter for Micro Shops Resilience? Evidence from Uganda. (January 2021) - Scuderi, Raffaele; Tesoriere, Giuseppe; Fasone, Vincenzo
This article analyzes the relationship between location and resilience of micro shops in Uganda. We use a unique city-level data set and consider the longevity of business as a proxy for resilience. After controlling for a set of relevant variables, our findings suggest positive correlation between longevity and proximity to Kampala, the capital city and vibrant commercial center of Uganda. We also find that entrepreneurship-related factors and natural events are further significant elements. We stress the importance to strengthen the integration between core and lagging areas as opposed to the current territorial development pattern. This calls for development models where the creation of satellite hubs and commercial platforms may positively influence the resilience of micro business.